Molecular Characterization and Genetic Diversity of Entomopathogenic Nematodes, Rhabditida: (Steinernematidae and Heterorhabditidae) in Valle del Cauca as a Source for Biological Control (2017)
Banana and plantain are edible fruit crops widespread in tropical and subtropical regions, with high importance as a source of energy, nutrients and incomes for lots of families in developing countries. The Musa genus comprises twenty-eight species where M. acuminata and M. balbisiana are the most important species for commercial purposes. However several diseases and pests affect the productivity and fruit quality generating considerable losses every year. Banana weevil complex species are one of the main responsible of such losses worldwide; nevertheless several attempts have been carried out to control banana weevil populations. Cosmopolites sordidus is the most frequent species reported worldwide and with more interest for population control. In the present study four banana weevil species (C. sordidus, Metamasius hemipterus, M. hebetatus, Polytus mellerborgii) were found associated to banana and plantain stands. Genetic analysis on banana weevil species, from mtDNA and nr DNA Loci, indicated a widespread of few haplotypes across 12 municipalities of Valle del Cauca, also a low number of alleles were found indicating a possible bottleneck mediated by human activities. dditionally a survey for entomopathogenic nematodes (EPN) associated to plantain and banana stands was made, were Steinernematids and Heterorhabditids species were found, however molecular characterization indicates a low genetic diversity in EPN isolates. Two nuclear Loci (ITS and LSU) were sequenced and employed for species identification, indicating that from 14 isolates obtained, 10 of them belonged to Steinernema carpocapsae and four to Heterorhabditis spp. For the latter there was contrasting results when either ITS or LSU región was employed for species identification, nevertheless a concatenated analysis showed the presence of two species, Heterorhabditis bacteriophora and Heterorhabditis sp. These indigenous EPN isolates could be promising for biological control of weevil banana complex species, since this isolates were found associated to plantain and banana stands and, together with the low genetic diversity found in weevil species, it is expected to develop strategies for pests management using EPN isolates obtained in the present study.